DAMPAK EROSI TEBING SUNGAI (STREAMBANK EROSION) TERHADAP PERUBAHAN PENGGUNAAN LAHAN PINGGIR BATANG BANGKO DI KABUPATEN SOLOK SELATAN - Agustian, Dani; Edial, Helfia; Zuriyani, Elvi (Pendidikan Geografi, 2013)
This study aims to analyze, collect, and process and describe the changes in river flow conditions caused by: 1) the condition of land use change caused by erosion of the river banks around the edge of the Batang Bangko, 2) the condition of river bank erosion caused by the river around the edge of the cliff rod Batang Bangko, 3) the speed of the river flow due to changes in land and river bank erosion 4) changes in stream flow direction Batang Bangko streambank erosion. This study uses a descriptive method that aims to explain, a portrait of the symptoms, the facts and the nature of the research area. The results showed that: 1) changes occur throughout Nagari land traversed by the Batang Bangko lengths vary between 87 m - 121 m. Changing land is paddy fields into streams. The main causes of land use change is the streambankerosion, 2) conditions along in general Bangko Batang is the streambanks. Streambank erosion caused by human activities in managing and treating nature.Activities Class C mining (sand and gravel) exploit many rivers and the surrounding areas, so that the carrying capacity of the streambank to decline, 3) Speed at Batang Bangko found diverse, thereby potentially streambank erosion along stream Batang Bangko. Average flow rate obtained at all points of observation ranged from 2.07 to 2.69 m / sec. As a result, the speed of the flow can also affect the river bank erosion in streams and Batang Bangko 4) Changes in flow direction of the river occurs at each sample point through which the Batang Bangko is also changing the varying distances 18-28 m and occurs in the left and the right of the river. Streams left turn into scrubland. The main causes of changes in flow direction of the flow is caused by human activity and the speed of the flow and the absence of vegetation land cover found on the riverbank.